Práticas pedagógicas e singularidades de estudantes da Educação de Pessoas Jovens e Adultas (EJA) - Mattos, Wanderlei Evaristo de (2020)
This work sought to understand the interfaces of the different curricular components to the Education of Young and Adult People (EJA) with the methodological universe present in the aforementioned teaching modality, based on the pedagogical practices developed by the teachers. The research sought to discuss how the teaching of different disciplines, based on the teaching practices reported in the narrative interviews by teachers from a school in the Municipal Network of São Bernardo do Campo (SP), seeks to be congruent with the singularities of the students' profiles in EJA in the heterogeneity of objectives, life histories and learning processes and rhythms, a fact that ends up challenging teachers and managers of School Units in their actions. In this study, the narrative interview is the main tool for the discovery and analysis of the experiences and experiences obtained by the teachers of the EMEB Bosko Preradovic school, and for them to discuss the possibilities of work methodologies that allow practical teachers to meet the students' singularities. Teachers narrated how they arrived at EJA (and the school studied), past and current practices, reflections on students and students and their goals and life perspectives, and made a self-reflection about their pedagogical practices, justifying how they managed to attend by they audience of such great diversity in different aspects.